Analisis Pengaruh Kualitas Layanan dan Customer Experience terhadap Keputusan Pembelian di Warkop Orla Sidoarjo - Romadhon, Iqbal; Maduwirnati, Ayun; Pujianto, Agung (STAI Denpasar Bali, 2025)
This study aims to examine the influence of Service Quality and Customer Experience on Purchase Decisions at Warkop Orla Gedangan Sidoarjo. The research employed a quantitative approach using multiple linear regression analysis. Based on the t-test results, the Service Quality variable (X1) yielded a t-value of 3.923, while the Customer Experience variable (X2) recorded a t-value of 4.067. Both values exceed the critical t-table value of 1.984, indicating that each variable has a significant impact on Purchase Decisions (Y). Consequently, the null hypotheses (H₀) are rejected and the alternative hypotheses (H₁) are accepted. These findings demonstrate that both service quality and customer experience play a crucial role in influencing consumer purchase decisions at Warkop Orla Gedangan Sidoarjo. The results suggest that management should pay close attention to enhancing both service quality and customer experience in order to increase consumer engagement and purchasing behavior. Keywords: Service Quality, Customer Experience, Purchase Decision, Warkop Orla